Pemahaman Karir Siswa Kelas XII IPA 1 SMA Negeri I Candung Kabupaten Agam - Putri Kurnia Ramadan; Budi Santosa (Education & Learning, 2021)
This career understanding actually aims to provide direction to students to live the next life. Here students still do not have the readiness to enter the world of work because of the limited knowledge and knowledge they have so far. However, students will attend lectures first to practice their abilities so that later they can carry out a job that has been chosen properly. This study aims to describe the career understanding of students of class XII IPA 1 SMA Negeri 1 Canduang.This study used a descriptive qualitative approach with 3 students as key informants and 1 BK teacher as supporting informants. In collecting data, researchers used the interview method. The data analysis technique used is data reduction, data display and data verification.Based on the results of the study, it can be concluded that this career understanding has been carried out well even though students still do not have the readiness to enter a world of work. In addition to understanding this career, students must also be able to understand: (1) Understanding themselves/self-understanding (2) understanding work (3) and also planning for the future. In understanding these 3 things students are able to understand themselves, for future planning students are able to plan future plans that will be lived later